(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
Height, weight of wood, vegetative growth rates in field and pot condition and a comparison of biomass of Jatropha curcas L. by using fertilizer and without fertilizer were studied. Results showed that although survival rate in pot condition was higher (58.06%) than that of field condition (49.14%), other biomass parameters were better in field condition. Average biomass of plants (dry weight) in pot condition was 62.09 g, and it was 209.28 g in field condition after one year. Associations among the parameters of biomass growth of the plant also studied here to show how the rate of change of length and diameter of stem, number of branches are interrelated in overall vegetative growth. Fertilizers used in the process of cultivation of J. curcas, better yield in terms of biomass production could be obtained than the condition where no fertilizer was used. Here on an average biomass of plants was 291.25 g without fertilizer and it was 683.75 g when fertilizers had been used. The extent of differences in all conditions are analyzed in the paper. Analysis and findings of this study might help to get information on better cultivation of J. curcas for mass production of this plant. Key words: Jatropha curcas L.; Vegetative growth; Biomass production; Fertilizer DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9603 BJSIR 2011; 46(4): 533-538